(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of computer network technology as a data communication medium is increasing. The need for simultaneous use of existing resources in the network both software and hardware has resulted in various technological developments on the network itself, Along with the increasing level number of network users who want to provide maximum results both in terms of efficiency and increased network security especially to support the staffing system of a company, based on these desires various parties continue to make improvements by utilizing various techniques, especially subnetting techniques and better use of hardware (including switches), so the concept of Virtual Local Area Network (VLAN) has emerged apply by IT(Information Tecnology) PROPAM POLDA of West Java to maintain its network system and to support its staffing system and official vehicle loan systems because VLAN provide management flexibility in making separate Virtual LANs into segments or subnets that can be used to define separate locations or networks network of departments in the PROPAM POLDA JABAR environment.